2020
DOI: 10.1007/s10554-020-01905-6
|View full text |Cite
|
Sign up to set email alerts
|

Reply to the letter to the editor: [Comment on “The relationship between atherogenic index of plasma and no-reflow in patients with acute ST-segment elevation myocardial infarction who underwent primary percutaneous coronary intervention]

Abstract: We have read with a great pleasure the letter of Dr. Cure et al. to the editor about our recent study which showed an association between atherogenic index of plasma (AIP) and no-reflow in patients with ST segment elevation myocardial infarction who underwent primary percutaneous coronary intervention. Dr Cure raises concerns about the miscalculation of AIP value that suggested choosing 'mmol/l' in equation instead of 'mg/dl'. As the AIP is the logarithmic transformation of triglyceride/ high density lipoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Russo et al in the Northern Manhattan Study of 675 patients showed that a value measured from 2D GLS for LV worse than –14.7% was a strong predictor of AF appearance [ 42 ], but this study was not concentrated on patients with HCM. Zegkos et al, in his recently published research concerning the relationship between 2D LV and LA strains and AF occurrence in the HCM population, defined the optimal cutoff values for the LV GLS (≥−14%) and LA strain (<20%) [ 43 ], which are very similar to that presented in our study.…”
Section: Discussionsupporting
confidence: 79%
“…Russo et al in the Northern Manhattan Study of 675 patients showed that a value measured from 2D GLS for LV worse than –14.7% was a strong predictor of AF appearance [ 42 ], but this study was not concentrated on patients with HCM. Zegkos et al, in his recently published research concerning the relationship between 2D LV and LA strains and AF occurrence in the HCM population, defined the optimal cutoff values for the LV GLS (≥−14%) and LA strain (<20%) [ 43 ], which are very similar to that presented in our study.…”
Section: Discussionsupporting
confidence: 79%
“…Thus, the diagnosis and management of COVID-19 have a high clinical significance. Elevation of cardiac enzymes such as cardiac troponin I and NT-proBNP are the early clues for the investigation of myocarditis [ 21 , 22 ]. While the endomyocardial biopsy is deemed the gold standard for the diagnosis of myocarditis [ 23 ], cardiac MRI is known as the gold-standard “imaging” modality for this condition [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the endomyocardial biopsy is deemed the gold standard for the diagnosis of myocarditis [ 23 ], cardiac MRI is known as the gold-standard “imaging” modality for this condition [ 24 , 25 ]. Different patterns of late gadolinium enhancement in COVID-19-associated myocarditis have been acknowledged in previous studies; nonetheless, it is mainly localized in the intramural or subepicardial regions of the left ventricle and the basal-to-mid inferolateral walls [ 22 , 26 ].…”
Section: Discussionmentioning
confidence: 99%